Teachers’ perspectives on determinants of educational (under)achievement of Cigano/Roma students in Portugal - Caetano, P.; Mendes, M. M.; Pinheiro, S.; Mourão, S.; Candeias, P.; Magano, O. (Intercultural Education, 2024)
The presence of Cigano/Roma students in secondary education in Portugal is still a rarity, considering that less than 3% of young Ciganos/Roma attend secondary education. This article aims to highlight the need for a comprehensive understanding of the perceptions of school teachers and principals on educational (under)achievement, absenteeism and school integration of Cigano students. To this end, we analyse data from an online questionnaire survey of a sample of 819 teachers, school principals and deputy principals and other senior management staff in schools of the Metropolitan Areas. These respondents express persistent representations and stereotypes in relation to the educational trajectories of Cigano students, especially in assigning prime causes of school failure to factors relating to the students’ family or own intrinsic issues, rarely indicating institutional factors or those linked to their teaching practices. Although this is a study centred on Portugal, the lessons drawn from it can point to new directions for other contexts, as the educational achievement of Cigano students represents an opportunity and an invitation to transform and upgrade school institutions as well as the educational system as a whole, which should be more innovative, reflexive and increasingly open to the community.